Single-cell gene expression reveals a landscape of regulatory T cell phenotypes shaped by the TCR - Zemmour, David (Nat Immunol, 2018)
CD4(+) T regulatory (T(reg)) cells are central to immune homeostasis, their phenotypic heterogeneity reflecting the diverse environments and target cells they regulate. To understand this heterogeneity, we combined single-cell RNAseq, activation reporter and TCR analysis to profile thousands of T(regs) or T(convs) from mouse lymphoid organs or human blood. T(reg) and T(conv) pools showed areas of overlap, as resting “furtive” T(regs) with overall similarity to T(conv), or as a convergence of activated states. All T(regs) express a small core of FoxP3-dependent transcripts, onto which additional programs are added less uniformly. Among suppressive functions, Il2ra and Ctla4 were quasi-constant, inhibitory cytokines being more sparsely distributed. TCR signal intensity didn’t affect resting/activated T(reg) proportions, but molded activated T(reg) programs. The main lines of T(reg) heterogeneity in mice were strikingly conserved in human blood. These results reveal unexpected TCR-shaped states of activation, providing a framework to synthesize previous observations about T(reg) heterogeneity.